2016
DOI: 10.1007/s10339-016-0757-6
|View full text |Cite
|
Sign up to set email alerts
|

Gesturing during mental problem solving reduces eye movements, especially for individuals with lower visual working memory capacity

Abstract: Non-communicative hand gestures have been found to benefit problem-solving performance. These gestures seem to compensate for limited internal cognitive capacities, such as visual working memory capacity. Yet, it is not clear how gestures might perform this cognitive function. One hypothesis is that gesturing is a means to spatially index mental simulations, thereby reducing the need for visually projecting the mental simulation onto the visual presentation of the task. If that hypothesis is correct, less eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…We argue that producing gestures offer stable visual and proprioceptive information regarding the hands in space, which allow a way to spatially index or "temporarily" locking simulated moves represented by the hand in space, thereby alleviating the relatively unstable visual imagery processes that would, otherwise, fulfill this tracking function. Indeed, in a companion study, we have found evidence that when participants with a lower visual working-memory capacity are instructed to gesture (or not to gesture) during mental preparation of the TOH, they produce less (or more) eye movements, suggesting that moving the hands allows for a way to stabilize simulations in a less visually demanding way (Pouw, Mavilidi, Van Gog, & Paas, 2016).…”
Section: Gesture-effect Hypothesismentioning
confidence: 99%
“…We argue that producing gestures offer stable visual and proprioceptive information regarding the hands in space, which allow a way to spatially index or "temporarily" locking simulated moves represented by the hand in space, thereby alleviating the relatively unstable visual imagery processes that would, otherwise, fulfill this tracking function. Indeed, in a companion study, we have found evidence that when participants with a lower visual working-memory capacity are instructed to gesture (or not to gesture) during mental preparation of the TOH, they produce less (or more) eye movements, suggesting that moving the hands allows for a way to stabilize simulations in a less visually demanding way (Pouw, Mavilidi, Van Gog, & Paas, 2016).…”
Section: Gesture-effect Hypothesismentioning
confidence: 99%
“…Participants' subsequent problem solving performance (i.e., solving speed) improved when they gestured during mental preparation (either spontaneously or instructed), but only when the TOH task was more difficult and when they had lower visual working memory capacity (determined via a Visual Patterns Test, explained below). In a subsequent study (Pouw, Mavilidi, van Gog, & Paas, 2016), it was found that adult participants (age 24-50 years) who were instructed to gesture during mental problem solving of the TOH, and especially those with a lower visual working memory capacity, were likely to reduce their eye movements during mental problem solving (as indicated by a drop in fixations directed at the TOH display when gesturing vs. not gesturing). This suggests that gesturing changes problem solving processes (as indicated by changes in eye-gaze behavior) as a function of internal cognitive resources available to solve the task (visual working memory capacity; see Pouw et al, 2016 for further discussion).…”
mentioning
confidence: 96%
“…In a subsequent study (Pouw, Mavilidi, van Gog, & Paas, 2016), it was found that adult participants (age 24-50 years) who were instructed to gesture during mental problem solving of the TOH, and especially those with a lower visual working memory capacity, were likely to reduce their eye movements during mental problem solving (as indicated by a drop in fixations directed at the TOH display when gesturing vs. not gesturing). This suggests that gesturing changes problem solving processes (as indicated by changes in eye-gaze behavior) as a function of internal cognitive resources available to solve the task (visual working memory capacity; see Pouw et al, 2016 for further discussion). Internal cognitive resources are thus to be taken into account when assessing effects of gesture on problem solving.…”
mentioning
confidence: 96%
“…Yet, we hasten to note that our prediction of the differential working memory support of depictive versus tracing gestures is about differences in degree of association, rather than assuming that depictive or tracing gestures is only related to either verbal or visual-spatial processing. Finally, we note that the choice for these specific working-memory capacity components is motivated by findings that verbal and visual working-memory capacity is predictive for the rate at which participants produce co-speech gestures (Chu et al, 2013;Gillespie et al, 2014; see also Pouw et al, 2016), providing some preliminary evidence (if our rationale is on track) that such working memory components might relate to gesture observation as well.…”
Section: Gesture and Cognitive Dispositionsmentioning
confidence: 99%